FAKTOR YANG MEMPENGARUHI KUNJUNGAN WISATA PADA OBYEK WISATA SENDANG ASRI WADUK GAJAH MUNGKUR WONOGIRI - Winarna Winarna; Nanik Irma Susanti (STIE AUB Surakarta, 2019)
Tourism Object Sendang Asri Gajah Mungkur Reservoir is the most visited tourist destinations compared to other tourist objects in the Wonogiri region. The uniqueness that is owned by the tourism object of Sendang Asri is often held certain events such as new year, Idul Fitri holidays, the title of cultural tourism and so on which at that time the number of visitors far beyond the ordinary day. Many factors affect the amount of tourist visits, especially in Tourism Object of Sendang Asri Gajah Mungkur Reservoir such as existing facilities, ease of location, uniqueness and service, price and beauty and scarcity of objects.This research aimed to test whether factors which researchers convey the above have effect excursions on tourism visit to tourism object of Sendang Asri Wonogiri. With this research is expected the manager can take strategy in managing this area. In this research into the object is the visitor of tourism object of Sendang Asri Gajah Mungkur Reservoir. Because of the limitations of the researchers, the researchers used samples with convenience Random Sampling. Data analysis techniques used were factor analysis with variable determination stage, correlation matrix formation, factor extraction, matrix rotation, model determination test and SWOT analysis. Expected research outputs are publications in International journals, Materials to be submitted in scientific meetings, simple Intellectual Property Rights and teaching materials lectures.